SDL 2011: Integrating System and Software Modeling 15th International SDL Forum Toulouse, France, July 5-7, 2011. Revised Papers - Ober, Iulian; Ober, Ileana; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book constitutes the thoroughly refereed post-conference proceedings of the 15th International SDL Forum, SDL 2011, held in Toulouse, France, in July 2011. The 16 revised full papers presented together were carefully reviewed and selected for inclusion in the book. The papers cover a wide range of topics such as SDL and related languages; testing; and services and components to a wide range presentations of domain specific languages and applications, going from use maps to train station models or user interfaces for scientific dataset editors for high performance computing.
Keywords: Computer science; Computer network architectures; Computer Communication Networks; Software engineering; Logic design; Information Systems; Computer Science; Computer Systems Organization and Communication Networks; Software Engineering; Logics and Meanings of Programs; Programming Languages, Compilers, Interpreters; Computer Communication Networks; Management of Computing and Information Systems